2001
DOI: 10.1121/1.1379087
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific fundamental and formant frequency patterns in a cross-sectional study

Abstract: Article:Whiteside, S.P. (2001) Sex-specific fundamental and formant frequency patterns in a cross-sectional study. The Journal of the Acoustical Society of America, 110 (1). pp. [464][465][466][467][468][469][470][471][472][473][474][475][476][477][478] https://doi.org/10.1121/1.1379087 eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
2
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 33 publications
5
78
2
6
Order By: Relevance
“…Compatibly, a study by Linville and Rens (2001) of long-term spectra from 80 speakers divided by age and gender showed a lowering of formants, especially of F1, from young adulthood to old age in both men and women. On the other hand, Meurer, Wender, Corleta, and Capp (2004) found less variation, but no lowering, of formants in older women while Rastatter et al (1997) found consistent lowering only in the first formant frequency: as in other studies (e.g., Whiteside, 2001), they also found that the formant changes between the older and younger speakers were vowel-dependent and that the age-related changes were different for male and female speakers. Finally, in Labov's (1994) analysis of the same person aged 68 and then 85, there was no evidence of any significant longterm change to F1 or F2 over these years.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Compatibly, a study by Linville and Rens (2001) of long-term spectra from 80 speakers divided by age and gender showed a lowering of formants, especially of F1, from young adulthood to old age in both men and women. On the other hand, Meurer, Wender, Corleta, and Capp (2004) found less variation, but no lowering, of formants in older women while Rastatter et al (1997) found consistent lowering only in the first formant frequency: as in other studies (e.g., Whiteside, 2001), they also found that the formant changes between the older and younger speakers were vowel-dependent and that the age-related changes were different for male and female speakers. Finally, in Labov's (1994) analysis of the same person aged 68 and then 85, there was no evidence of any significant longterm change to F1 or F2 over these years.…”
Section: Introductionsupporting
confidence: 67%
“…There are a small number of studies that are consistent with this view. These include Xue and Hao (2003) who recently showed a lowering of formant frequencies, particularly of F1, in elderly speakers of both genders, and Whiteside's (2001) reanalysis of the data in Lee, Potamianos, and Narayanan (1999) of 436 children and 56 adults who also showed formant lowering with increasing age. Compatibly, a study by Linville and Rens (2001) of long-term spectra from 80 speakers divided by age and gender showed a lowering of formants, especially of F1, from young adulthood to old age in both men and women.…”
Section: Introductionmentioning
confidence: 99%
“…Up to recently this has been the only description used in applications as Pathology Detection [20] influence from voice and to produce reliable estimates of the Glottal Source. It is also useful in certain speaker characterization studies, as age or gender [22].…”
Section: Structured Parameterization Of Voicementioning
confidence: 99%
“…16, exp. [21][22] to refer to the low-frequency contents of the signal under analysis. In the present case as by [14] (exp.…”
Section: Another Iteration Is Started Using a Subordinate Lattice Filmentioning
confidence: 99%
“…Además, se agrupó a los participantes por sexo, puesto que, a pesar de que los efectos de la maduración vocal se hacen más evidentes en la adolescencia (Whiteside, 2001;Whiteside, Hanson y Cowell, 2004), se observaron diferencias significativas entre las niñas y los niños de este estudio (véanse los resultados recogidos en la Tabla 4 y en la Tabla 5). A continuación, se refleja toda esta información en la Tabla 1.…”
Section: Poblaciones De Estudio Y Muestras Vocálicasunclassified